Optimal switching control of flow in PV/T systems with forced circulation - Siecker, Juan (Bloemfontein: Central University of Technology, Free State, 2018)
Cooling the operating surface is a key operational factor to take into consideration to achieve higher efficiency when operating solar photovoltaic systems. Appropriate cooling may improve the electrical efficiency and decrease the rate of cell degradation with time, resulting in maximization of the life span of photovoltaic modules. The excessive heat removed by the cooling system can be used in domestic, commercial or industrial applications. The hybrid photovoltaic/thermal (PV/T) system cooled by forced water circulation is one of the most efficient methods used to improve the electrical performance of a PV module. These systems operate mostly on the principle in cooling the PV module at a constant flow rate. However, the optimal PV output power cannot be achieved due to the circulating water not absorbing most of the heat on the surface of the PV module. In order to solve this problem, a mathematical model dealing with the optimal switching of flow in PV/T systems with forced circulation has been developed, with the aim of controlling the surface operating temperature whilst increasing the conversion efficiency. The optimal switching control model is used to reduce the surface operating temperature of the PV module, where it is simulated by making use of the SCIP (Solving Constrained Integer Programs) solver in the optimization toolbox in MATLAB. The simulation results illustrate that the optimal switching control of flow may improve the electrical output power of a PV module, as well as effectively reducing the surface temperature thereof. Furthermore, an economic feasibility study was performed to compare these systems, where the optimal switching control strategy has a significantly higher initial capital cost compared to the standard PV system. However, when studying both systems over their predicted lifetime, the optimal switching control strategy generates a significantly higher profit, regardless of its extortionate initial capital cost, and is, therefore, the ultimately efficient system.
Published Thesis
Keywords: Photovoltaic/thermal (PV/T) system; optimal switching control; cooling technologies; flat plate collector